Regulation of postharvest inflorescence senescence in Arabidopsis thaliana : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Science at Massey University, Palmerston North, New Zealand - Xu, Xi (Massey University, 2020)
Senescence is critical for plant survival and fitness as it ensures the most efficient use of nutrients for development and production of offspring. Senescence is a genetically controlled and hormone-mediated programme. Besides being induced in an age-dependent manner, senescence can also be initiated precociously from harvest-induced stress such as light- and sugar-deprivation. Understanding the biological mechanisms behind dark-mediated senescence is important as it helps to provide a new strategy for extending shelf life of crop plants. This project aims to understand the regulation of dark-induced inflorescence senescence in model plant Arabidopsis thaliana by using a forward genetic approach. Arabidopsis mutants showing accelerated and delayed inflorescence senescence (named ais and dis) were identified previously. Here, I rescreened 23 mutants and confirmed the altered time to senescence phenotype of nine mutants, including two ais and seven dis mutants. Of those, the dis2, dis9, dis15 and dis51 mutants were used for further analysis. The delayed degreening phenotype was also observed in detached dark-held leaves of dis2 and dis51 mutants, indicating that the causal mutations affected genes that regulate both leaf and inflorescence senescence. Segregation analysis was used to determine the genetic nature of dis traits in the dis2 and dis51 mutants. The dis2 trait was found to be monogenic recessive while the dis51 trait is dual-genic recessive. The dis2 mutant showed an extended “stay-green” phenotype and retained higher chlorophyll (Chl) b than Chl a. These findings were consistent with a lesion in the NON-YELLOW COLORING1 (NYC1) gene. Sequencing revealed a C/T transition in exon 8 of NYC1, which caused a highly conserved proline to be substituted by serine at amino acid position 360 of the NYC1 protein. By contrast, dis51 retained a similar amount of Chl a and Chl b. One of the genetic lesions in this mutant was mapped to a ~665 kb region at the top arm of chromosome 5 by using High Resolution Melt (HRM)-based mapping technology. The ETHYLENE INSENSITIVE2 (EIN2) gene was considered as a promising candidate because similar phenotypes were observed in ein2 mutants and dis51 seedlings did not show triple response when treated with the ethylene precursor ACC in the dark. PCR-based sequencing showed a G to A mutation in exon 6 of EIN2, resulting in a premature stop codon, which thereby resulted in a truncated EIN2 protein missing part of the C-terminal region that is required for ethylene signal transduction. In addition, the dis51 mutant emitted a pleasant aroma, which is abnormal in Arabidopsis. Four compounds (benzaldehyde, benzyl alcohol, phenylacetaldehyde and phenylethanol) were detected by using GC-MS analysis. However, it is not clear if the mutation causing the aroma phenotype also contributed to the dis51 phenotype. The mutations in the dis9 and dis15 mutants were previously mapped to chromosome 3 and chromosome 2, respectively. Here, further HRM and whole genome sequencing (WGS) data analyses were used to identify the causal mutation in the dis9 mutant. The mutation changed a highly conserved Ser-97 to Phe in the active site of strigolactone (SL) receptor gene DWARF14 (D14), likely causing loss-of-activity. Since dis15 showed similar phenotypes to dis9, I hypothesised that the genetic lesion in dis15 may also have occurred in an SL pathway gene. The MORE AXIALLY GROWTH1 (MAX1) SL biosynthesis gene was present within the previously mapped region of this mutant. By using WGS data, I found a G/A mutation in the coding region of MAX1. The mutation in MAX1 substituted a highly conserved Gly-469 (G469) with Arg (R) in the haem-iron ligand signature of the Cytochrome P450 proteins. Using a N. benthamiana transient expression system, I found that the G469R substitution caused loss-of-activity of MAX1. In addition, the delayed sepal degreening of dis9 and dis15 was also observed in planta, suggesting a role of SL in regulation of both developmental and dark-induced sepal/inflorescence senescence. nCounter transcript counting technology was used to investigate the relationship between SL biosynthesis and signalling, sugar signalling and dark-induced senescence. There was no evidence of SL biosynthesis during the normal night in the inflorescences. During the extended night, the expression patterns of the SL biosynthetic gene MAX3 and signalling gene SUPPRESSOR OF MAX2-LIKE7 (SMXL7) best correlated with the sugar-responsive senescence regulatory genes [ARABIDOPSIS NAC DOMAIN CONTAINING PROTEIN92 (ANAC092) and NAC-LIKE, ACTIVATED BY AP3/PI (NAP)] and senescence marker gene (SENESCENCE-ASSOCIATED GENE12; SAG12), suggesting an interaction between SL and sugar signalling in controlling dark-induced inflorescence senescence. ANAC092 and NAP were further induced in the max1 mutant by the SL analogue, GR24, suggesting they are SL-inducible genes. The overall findings in this project reflect a complex regulatory network, which involves multiple phytohormones and degradation pathways, during dark-induced inflorescence senescence in Arabidopsis. Here, I proposed a model in which prolonged darkness first causes sugar-starvation in the excised inflorescence; the plant hormones ethylene and SL subsequently work together to regulate inflorescence senescence, including NYC1-regulated Chl degradation.
Figures are re-used with permission.
Keywords: Arabidopsis thaliana; Aging; Genetics; Postharvest physiology; Effect of stress on; Inflorescences; 310806 Plant physiology